Reading Mohammed ben Abdallah’s The Slaves and Monique Mojica’s Princess Pocahontas and the Blue Spots as Re-Visionary Historical Dramas - Dannabang Kuwabong (European Journal of American Studies)
This paper is a comparative reading of Indigenous Canadian and Ghanaian drama as acts of faithful witnessing that function as resistance to colonial histories of erasures of colonized peoples in Ghana and North America. I contemplate that while Mojica’s play provides the ritual space to testify against multiple coloniality layered in the histories of slavery, genocide, land dispossession, and the cultural erasure committed against Indigenous peoples of Canada, Mohamed Ben Abdallah’s plays stage a recall of the traumatic history of the Trans-Atlantic and Trans-Saharan slave trades, genocides, multiple dislocations, cultural deracination, and identity erasures that continue to haunt the people of West Africa. The study explores postcolonial dramaturgical and theatrical elements such as dance, storytelling, music, and rituals in Princess Pocahontas and the Blue Spots and The Slaves.